AN INVESTIGATION OF SAUDI TEACHERS’ PERCEPTIONS TOWARDS TRAINING IN COOPERATIVE LEARNING - Almulla, Mohammed (PEOPLE: International Journal of Social Sciences, 2016)
Cooperative Learning (CL) approaches have been widely researched in a number of educational contexts and a various studies indicate the effectiveness of using them to improve learners’ social and academic performance when working in small cooperative groups. However, there is still relatively little research on teacher training on CL and teachers perceptions of such training programmes. Investigations on challenges teachers face when start using CL in class or on factors that help overcome such challenges are also relatively few. This paper presents some of the results of a case study conducted in an all-male high school in Saudi Arabia. This article discusses participant-teachers’ perceptions towards the training in cooperative learning they received as well as their perceptions of the initial challenges the implementation of CL posed when working in a country where education still relies heavily on lecture style transmission and memorisation. Qualitative data was collected from eight participant-teachers by using semistructured individual interviews. The data was then submitted to thematic analysis using inductive and deductive analytical approaches. The findings suggest that preservice and in-service training, also referred to as Continuing Professional Development (CPD), in cooperative learning are important to help teachers change their perceptions towards training as well as their views on classroom roles,responsibility and authority. However, data also shows that are considerable initial challenges that teachers face during the period in which a change from lecture style to CL is taking place. Besides the training programme, it is important to consider the factors that can help to overcome these challenges and difficulties.